1989
DOI: 10.1007/bf00004219
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and nutrient loading by precipitation in the Trachypogon savannas of the Orinoco llanos, Venezuela

Abstract: Samples of bulk precipitation were collected in the Trachypogon savanna, Calabozo, Venezuela, during three consecutive years. In the first year, rain samples were taken daily; in the following years the samples were grouped on a monthly basis. In addition, samples of dry deposition were collected during the dry seasons. All samples were analyzed for the following water soluble cations and anions: PO,-P, SO 4 -S, NO,-N, NH 4 -N, Ca+2, Mg + 2 , K +, Na + and H + . The mean annual input rate of chemical constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Our estimates of wet atmospheric deposition of N and P based on literature data from East Africa and our own measurements were in line with values reported for other savanna ecosystems (1.3-6.4 kg N and 0.3-0.5 kg P ha -1 y -1 ) (Montes and San Jose 1989;Chacon and others 1991;Sanhueza and Crutzen 1998;Laclau and others 2005;Bustamante and others 2006). Dry deposition is likely to be minimal in our study area because the prevailing winds come from the Indian Ocean; this was also found for a coastal savanna in Congo (Laclau and others 2005).…”
Section: Nutrient Input and Output Fluxes And Balancessupporting
confidence: 90%
“…Our estimates of wet atmospheric deposition of N and P based on literature data from East Africa and our own measurements were in line with values reported for other savanna ecosystems (1.3-6.4 kg N and 0.3-0.5 kg P ha -1 y -1 ) (Montes and San Jose 1989;Chacon and others 1991;Sanhueza and Crutzen 1998;Laclau and others 2005;Bustamante and others 2006). Dry deposition is likely to be minimal in our study area because the prevailing winds come from the Indian Ocean; this was also found for a coastal savanna in Congo (Laclau and others 2005).…”
Section: Nutrient Input and Output Fluxes And Balancessupporting
confidence: 90%
“…A similar value of 2.2 kg ha )1 yr )1 was reported for the input of inorganic N from bulk precipitation and dry deposition in a Trachypogon savanna in Venezuelan Llanos (Montes and San Jose 1989). The input of NH 4 -N was 2.0 kg ha )1 yr )1 , but organic nitrogen input was not measured.…”
Section: Atmospheric Depositionsupporting
confidence: 70%
“…The reported inputs of inorganic N in the South American savannas are lower than the values found in an African savanna ($5 kg ha )1 yr )1 ) (Villecourt and Roose 1978 cited by Abbadie et al 1992). Comparing atmospheric deposition inputs and the amount of N in above-and belowground plant biomass in a Trachypogon savanna, Montes and San Jose (1989) suggested that 19.5% of the N required for maximum biomass of 482 g m )2 during growth season was supplied by atmospheric deposition. They pointed out that the distribution of rains seemed to determine essential differences in the nutrient inputs, as the ratio of the nutrient input during the rainy and the dry season ranged from 2.3 to 7.8.…”
Section: Atmospheric Depositionmentioning
confidence: 99%
“…Venezuelan and Colombian flooded savannas are characterised by acidic soils and also by redox conditions which may induce Zn and Cu solubilisation; losses by leaching and external run-off (erosion) might reach limiting levels unless they are compensated for by the inputs due to precipitation or by weathering of Zn and Cu accessory minerals. Precipitation water in neotropical savanna ecosystems is in general slightly or definitely acid [4,5], therefore, macro and micronutrient levels in such water are not expected to be particularly high. Moreover, savanna ecosystems, and within them, alluvial overflow plains in Venezuela are distant from the ocean and with a non-significant anthropogenic activity; consequently the composition of rain water should be minimally affected by marine aerosols.…”
Section: Introductionmentioning
confidence: 98%